Fundamentals of project management [ - Heagney, Joseph (WorkSmart series, 2012)
"With sales of more than 160,000 copies, Fundamentals of Project Management has helped generations of project managers navigate the ins and outs of every aspect of this complex discipline. Using a simple step-by-step approach, the book is the perfect introduction to project management tools, techniques, and concepts. Readers will learn how to: -- Develop a mission statement, vision, goals, and objectives -- Plan the project -- Create the work breakdown structure -- Produce a workable schedule -- Understand earned value analysis -- Manage a project team -- Control and evaluate progress at every stage. Fully updated based on the latest version of the Project Management Body of Knowledge (PMBOK), the fourth edition contains new information and expanded coverage on the project risk plan; the change control process; the concept of the project manager as leader; and more. This up-to-the-minute guide is filled with tips and techniques for planning and executing projects on time, on budget, and with maximum efficiency."--Provided by publisher.